The Legal Regulation of the Expiry of Training and Qualification Contracts in the Saudi Labor System: An Analytical Study - Wad Sanat Alotaibi (International Journal of Law Research and Studies, 2025)
The training and qualification contract is one of the most important employment contracts. Given its connection to the skills, capabilities and experiences that this contract provides to the worker and its being a development tool that contributes to building human competencies for the Saudi labor market, therefore, regulating the provisions of this contract and its regulatory effects has become a requirement in the Saudi labor system. This study was divided into two sections. In the first section, the nature of training and qualification contracts, their substantive and formal conditions, and the legal and constitutional basis for this contract were defined. In the second section, we addressed the legal regulation of the rules for the expiration of the training and qualification contract. Therefore, this study focused on clarifying the provisions of training and qualification contracts, specifically the provisions for the expiration of training and qualification contracts in the Saudi labor system. The main problem of this research is the lack of a special legal regulation for the provisions for the expiration of training and qualification contracts except in one case specified by Article (48) of the Saudi labor system, which is the authority to terminate the training and qualification contract by the employer by unilateral will if it is proven that the worker is unable and unsuitable to achieve the training objectives. The same applies to the worker, as he can terminate by unilateral will, but he did not set conditions for this termination. Accordingly, the regulator was satisfied with the previous termination case. However, other cases may occur, such as death, force majeure, emergency circumstances, bankruptcy, and other cases that must be stipulated in the labor system, as these cases entail effects and entitlements for the worker and the employer, and it is feared that they will be lost. The regulator did not refer to the general rules for terminating employment contracts, given the text of the article, which led to a legislative deficiency that must be corrected. We concluded from this study with a set of recommendations and proposals that include a request to allocate a special legal regulation for the issue of terminating training and qualification contracts as soon as possible, including the following cases: the case of the final closure of the training facility, the bankruptcy of the training entity, force majeure, emergency circumstances, the end of the training activity, the end of the training period, and other cases subject to the general rules for terminating the employment contract in the Saudi labor system. Also, when looking at the provisions of the training and qualification contract, the Saudi regulator only stipulated formal controls and conditions, and was silent about regulating objective conditions related to the trainee worker, such as contractual eligibility and determining the maximum age of the trainee worker when concluding the training and qualification contract, also with regard to moral guarantees related to the worker, for example, the absence of a criminal record against him and the absence of a conviction against him. For a crime involving dishonesty and breach of trust.